2003
DOI: 10.1021/la0266381
|View full text |Cite
|
Sign up to set email alerts
|

Why Is It Much Easier To Nucleate Gas Bubbles than Theory Predicts?

Abstract: Bubble nucleation from supersaturated gas solutions generally takes place at much lower supersaturations than are expected from the theory. Furthermore, the same theory predicts that the threshold concentration of gas needed to cause nucleation should be essentially independent of the gas species used, a finding contradicted by experiment. There are two general explanations:  first, that the theory is wrong, or second, that there is a previously unidentified factor which is influencing the results of the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 51 publications
(53 reference statements)
5
147
1
1
Order By: Relevance
“…The range of total gas content values for our samples was 1.6 to 6.5 mL L −1 , which is in the lower end of ranges reported by Matsuo and Miyake (1966), Tison et al (2002) and Crabeck et al (2014b). Zhou et al (2013) suggested that gas transport through sea ice occurs via processes diverging from those controlling the transport of salt.…”
Section: The Fate Of Gas Vs the Fate Of Saltcontrasting
confidence: 48%
See 2 more Smart Citations
“…The range of total gas content values for our samples was 1.6 to 6.5 mL L −1 , which is in the lower end of ranges reported by Matsuo and Miyake (1966), Tison et al (2002) and Crabeck et al (2014b). Zhou et al (2013) suggested that gas transport through sea ice occurs via processes diverging from those controlling the transport of salt.…”
Section: The Fate Of Gas Vs the Fate Of Saltcontrasting
confidence: 48%
“…Where the brine volume exceeds the permeability threshold for columnar ice of 5 % V b (Golden et al, 1998(Golden et al, , 2007, the ice layer is referred to as permeable. curs when SAT f > 1, so these subsaturated layers should be bubble-free, though bubble nucleation from saturated gas solutions has been observed at much lower saturations than theoretically expected (Lubetkin, 2003). On 14 January, 75 % of the bubbles observed were located in subsaturated permeable bottom layer of columnar sea ice.…”
Section: Bottom Permeable Columnar Icementioning
confidence: 77%
See 1 more Smart Citation
“…The association of polymers containing a large number of hydrophobic pendant groups, for example polymer HC10-h, may further strengthen polymer adhesion to bubbles. The grouping of the hydrophobic regions can also facilitate bubble nucleation via catalytic effects offered by the hydrophobic zones (Lubetkin, 2003), leading to bubbles formed with polymers in situ. When bubbles are formed in the presence of the polymer, little to no diffusion is required to associate a polymer to its surface.…”
Section: Mechanisms Of Cell Removal In Posidafmentioning
confidence: 99%
“…Lubetkin [62] presented a list that illustrates the variety of arguments that have been put forward to explain the discrepancies between nucleation theory and experiments. The supersaturation ratio in the Champagne example is low compared to the theoretical predictions of ζ > 1000 in order for homogeneous nucleation to occur at room temperature [63].…”
Section: Bubble Nucleationmentioning
confidence: 99%